Health Checkup Behavior of Elderly with High Risk of Heart Disease - Habeahan, Natamia Kyrieleison; Juniarti, Neti; Mulya, Adelse Prima (Indonesian Journal of Global Health Research, 2024)
Health complaints that are often felt by the elderly such as coughs, fever, heat, diarrhea, headaches, and even complaints of disability, accidents, and chronic diseases that have been suffered. One of them is cardiovascular disease, namely heart disease which is a non-communicable but very deadly disease. Indonesia has a prevalence of heart disease that has tripled from 2013 to 2018 so this study aims to determine health examination behavior to identify the proportion of elderly people who have a high risk of heart disease. This study uses quantitative research with descriptive methods with a cross sectional study approach. The distribution of elderly behavior in conducting routine health checks was 52 (57.1%). There were 72 (79.1%) elderly with hypertension, 53 (58.2%) with high blood cholesterol and 10 (11%) with high blood sugar. These results explain that the high risk of heart disease in the elderly is still very high, therefore the behavior of the elderly in Jatinangor especially at Cipacing and Cilayung are really needs to be improved. The results of blood pressure checks, blood cholesterol levels and abnormal blood sugar levels need attention for health workers in the public health center area.